Domestic Dogs and Wild Foxes Interactions in a Wildlife-Domestic Interface of North-Central Chile: Implications for Multi-Host Pathogen Transmission - Hernández, Felipe A.; Manqui, Jonatan; Mejías, Carlos; Acosta-Jamett, Gerardo (Frontiers in Veterinary Science, 2021)
Domestic dogs (Canis familiaris) often cohabite at interfaces shared by humans and wildlife, interacting with wild canids as predators, prey, competitors and reservoirs of several multi-host pathogens, such as canid-borne micro and macro parasites that could impact on wildlife, livestock and public health. However, spatio-temporal patterns of indirect interactions as promoters of pathogen transfer between domestic and wild canids are largely unknown. In this study, we used camera traps to describe the activity patterns and habitat use of dogs, chilla (Lycalopex griseus) and culpeo (Lycalopex culpaeus) foxes and identify the local-scale factors that may affect the frequency of dog-fox interactions through an anthropization gradient of the Coquimbo region, Chile. We assessed local-scale variables that may predict the number of interactions between dogs and foxes, and compared the time interval between dog-culpeo and dog-chilla interactions. Our findings suggested that closeness to urbanized zones predicts the frequency of indirect interactions between dogs and foxes. We found higher number of dog-fox interactions (60 interactions) at a periurban site adjacent to two coastal towns (Tongoy and Guanaqueros), compared to other two more undisturbed sites (12 interactions) increasingly distanced from urbanized areas. We showed that dogs interacted more frequently with chilla foxes (57 interactions) than with culpeo foxes (15 interactions), and the first interaction type occurred almost exclusively at the periurban site, where dogs and chillas were more frequently detected than in the other sites. We detected a marked temporal segregation between dogs and foxes, but dog-chilla interactions resulted in shorter time intervals (2.5 median days) compared to dog-culpeo interactions (7.6 median days), suggesting a higher potential risk of pathogen spillover between the first species pairing. Based on previous studies, we suggest periurban zones may constitute a potential focus of pathogen exposure between dog and fox populations in the study area. Our research contributes to improving the knowledge on the spatio-temporal patterns of interspecific contact between invasive and native carnivores within the context of multi-host pathogen dynamics. Our outcomes will inform theoretical epidemiological models designed to predict and minimize the contact risk between domestic and threatened species, guiding effective control strategies at the wildlife-domestic interface.